2001
DOI: 10.4269/ajtmh.2001.65.783
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bartonella species and 16s rRNA gene types of Bartonella henselae from domestic cats in Thailand.

Abstract: Abstract. Prevalence of Bartonella infection among 275 cats in 9 sites from 4 geographical regions (northern area: Chiang Mai; central area: Kanchanaburi, Ratchaburi, and Bangkok; northeastern area: Khon Kaen, Roi Et, Ubon Ratcharthani, and Nakhonratchasima; southern area: Songkhla) of Thailand was investigated. Overall, Bartonella species were isolated from 27.6% (76 of 275) of the cats. The isolation rate varied from 12.8% (5 of 39) in Songkhla (southern area) to 50.0% (26 of 52) in Khon Kaen (northeastern a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 28 publications
6
50
2
2
Order By: Relevance
“…6,[23][24][25][26][27] In this study, the rate of co-infection (4.8%) of B. henselae and B. clarridgeiae in our flea samples was low when compared with high rates (approaching 90%) reported in a previous study. 6 The genogroups of B. henselae vary in human and animal samples in different geographic regions.…”
mentioning
confidence: 71%
“…6,[23][24][25][26][27] In this study, the rate of co-infection (4.8%) of B. henselae and B. clarridgeiae in our flea samples was low when compared with high rates (approaching 90%) reported in a previous study. 6 The genogroups of B. henselae vary in human and animal samples in different geographic regions.…”
mentioning
confidence: 71%
“…A B . clarridgeiae prevalence of 17% to 36% among all Bartonella isolates was reported in studies conducted in France, the Netherlands, the Philippines, and Thailand ( 2 , 22 ). However, B .…”
Section: Feline Bartonella Speciesmentioning
confidence: 89%
“…Both B. henselae and B. clarridgeiae have been isolated from cats in some of these countries, including Indonesia, Thailand, Philippines and Japan [8,24,26,27]. The prevalence of bacteremia ranged from 6.4% to 89% for B. henselae [8,[25][26][27] and 0.7% to 31% for B. clarridgeiae [8,26,27]. Co-infection with B. henselae and B. clarridgeiae were reported in cats from the Philippines and Japan [8,26].…”
Section: Introductionmentioning
confidence: 99%
“…In Asian countries, the results showed that seroprevalence of B. henselae among cat populations in Japan ranged from 9.1 to 15.1% [28,36], 68% in Philippines [8], 48% in Singapore [29] and 54% in Indonesia [24]. Both B. henselae and B. clarridgeiae have been isolated from cats in some of these countries, including Indonesia, Thailand, Philippines and Japan [8,24,26,27]. The prevalence of bacteremia ranged from 6.4% to 89% for B. henselae [8,[25][26][27] and 0.7% to 31% for B. clarridgeiae [8,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation